Premenstrual Dysphoric Disorder Causes Discomfort And Interfere Adolescent’s Social Relationship - Dewi Marfuah (Alma Ata University Press, 2018)
Menstruation is the discharge of blood from the uterus through the vagina which happens monthly. Premenstrual syndrome (PMS) is one of menstrual disorder and a health problem in reproductive women with prevalence about 20-40%. While, Premenstrual Dysphoric Disorder (PMDD) is severe form of PMS with prevalence about 3-8%. Prevalence of PMS and PMDD increased in Pasca of disaster area about 47,3% and 41,8%. However, no researches aim to describe about life experience of adolescence with PMDD’s syndromes in pasca of disaster area. This study aimed to describe adolescents’s experience who experiencing symptoms of PMDD. This study used a qualitative study with phenomenological approach. Number of participants were six female students of SMK Negeri 1 Cangkringan, Yogyakarta, Indonesia that meet PMDD based on the Diagnostic and Statistic Manual of Mental Disorders DSM-IV. In-depth interviews with a unstructured interview and using Colaizzi method for analysis data. Thus for trustworthiness with data source triangulation to their teachers and classmates. The results found four main themes describing the experience of adolescence with PMDD’s syndromes were formed: symptoms perceived as a change that affects the psychological, behavioral and physical; symptoms are intermittent along the menstrual cycle; environmental and hormonal factors play a role in the onset of symptoms; and symptoms cause discomfort and interfere social relationships of adolescents. Adolescents's experience with symptoms of PMDD post-disaster as like as the normal condition that cause discomfort that interferes adolescent’s social relationship. Nurses and other media personnel in the health care institution is expected to more actively participate to provide a wide range of related reproductive health education and giving intervention to reduce PMDD in order to increasing Women’s Quality of Life.